A Cross-Sectional Study on Nursing Preceptors' Perspectives About Preceptorship and Organizational Support - Rasha Ibrahim MSc, PhD; Manju Varghese PhD; Said Saleh Salim MSc (SAGE Publishing, 2024)
Background A skilled and experienced preceptor enhances nursing candidates' education. Students can acquire invaluable insights by observing and learning from the preceptor's professional nursing practice. Organizations must furnish sufficient support to guarantee the efficacy of preceptors in their responsibilities. Objective To evaluate preceptors' perceptions of the preceptorship and the relationship between organizational support and preceptor perspective of preceptorship. Methods A cross-sectional correlational design was deployed using purposive sampling of 90 nurses in the UAE. Between August 2023 and December 2023, a self-reported questionnaire with 40 items on preceptor perspectives of preceptorship (PPP) was distributed to nurses. The student's t-test, Chi-square, Monte Carlo, Fisher Exact, and Pearson coefficient were used. Results The results revealed that most participants were female (71.1%), with 48.9% between 36 and 45 years old. The mean score for the PPP was high (73.81 ± 10.92). There was a significant association between age, years of nursing experience, work area, and overall PPP. A strong correlation was found between self-preparation ( r  = .675), preceptorship perception commitment ( r  = .762), and the benefits of preceptorship ( r  = .830), along with organizational support. Conclusion The preceptors in this study had a positive perspective about preceptorship. Their acknowledgment of preceptorship's benefits to the organization shows their optimism and dedication. Future studies should analyze preceptor training programs and devise initiatives to improve clinical teaching.